Examining Students’ Questioning Strategies in EFL Classroom Interaction - Masyruha, Masyruha (Universitas Negeri Makassar, 2018)
The study on examining students’ questioning strategies in EFL classroom interaction is aimed at investigating: (1) the types of students questioning strategies that appeared in the EFL classroom interaction; (2) the levels of students questioning strategies that appeared in the EFL classroom interaction; and (2) the students perceptions regarding to their questions strategies in the EFL classroom interaction. This research employed descriptive qualitative research. It applied purposive random sampling technique in selecting sample. The participants of this research were a class C of third semester English students at Graduate Program of English Education Department in State University of Makassar of academic year 2018/2019. The data were collected by employing video recording and interview. The obtained data was scripted and analyzed based on interactive model of namely: (1) data reduction, (2) data display, and (3) conclusion drawing and verification. The results of this research showed that; (1) the types of students questioning strategies that appeared in the EFL classroom interaction are referential questions and display questions; (2) the level of students’ questioning respectively lies out on higher and lower level of cognitive questions which divided into three level; remembering, understanding and applying; (3) each students has different perception regarding the questioning strategies. Some students ask questions because they did not understand the material discussed while the other students ask questions only because the topic is interesting. Furthermore, in asking questions, majority of students write down in their questions first to make sure that their questions is suitable with the topic. Finally, each student has different ways to make sure that the presenter understands regarding their questions.